5-HTP inhibits eosinophilia via intracellular endothelial 5-HTRs; SNPs in 5-HTRs associate with asthmatic lung function - Walker, Matthew T.; Bloodworth, Jeffrey C.; Kountz, Timothy S.; McCarty, Samantha L.; Green, Jeremy E.; Ferrie, Ryan P.; Campbell, Jackson A.; Averill, Samantha H.; Beckman, Kenneth B.; Grammer, Leslie C.; Eng, Celeste; Avila, Pedro C.; et al. (Frontiers in Allergy, 2024)
Background: Previous research showed that 5-hydroxytryptophan (5HTP), a metabolic precursor of serotonin, reduces allergic lung inflammation by inhibiting eosinophil migration across endothelial monolayers. Objective: It is unknown if serotonin receptors are involved in mediating this 5HTP function or if serotonin receptor (HTR) single nucleotide polymorphisms (SNPs) associate with lung function in humans. Methods: Serotonin receptor subtypes were assessed by qPCR, western blot, confocal microscopy, pharmacological inhibitors and siRNA knockdown. HTR SNPs were assessed in two cohorts. Results: Pharmacological inhibition or siRNA knockdown of the serotonin receptors HTR1A or HTR1B in endothelial cells abrogated the inhibitory effects of 5HTP on eosinophil transendothelial migration. In contrast, eosinophil transendothelial migration was not inhibited by siRNA knockdown of HTR1A or HTR1B in eosinophils. Surprisingly, these HTRs were intracellular in endothelial cells and an extracellular supplementation with serotonin did not inhibit eosinophil transendothelial migration. This is consistent with the inability of serotonin to cross membranes, the lack of selective serotonin reuptake receptors on endothelial cells, and the studies showing minimal impact of selective serotonin reuptake inhibitors on asthma. To extend our HTR studies to humans with asthma, we examined the CHIRAH and GALA cohorts for HTR SNPs that affect HTR function or are associated with behavior disorders. A polygenic index of SNPs in HTRs was associated with lower lung function in asthmatics. Conclusions: Serotonin receptors mediate 5HTP inhibition of transendothelial migration and HTR SNPs associate with lower lung function. These results may serve to aid in design of novel interventions for allergic inflammation.